Use of an anti‐CD200‐blocking antibody improves immune responses to AML in vitro and in vivo. (30th September 2020) - Rastogi, Namrata; Baker, Sarah; Man, Stephen; Uger, Robert A.; Wong, Mark; Coles, Steven J.; Hodges, Marie; Gilkes, Amanda F.; Knapper, Steven; Darley, Richard L.; Tonks, Alex
Summary: Treatment of relapsed/resistant acute myeloid leukaemia (AML) remains a significant area of unmet patient need, the outlook for most patients remaining extremely poor. A promising approach is to augment the anti‐tumour immune response in these patients; most cancers do not activate immune effector cells because they express immunosuppressive ligands. We have previously shown that CD200 (an immunosuppressive ligand) is overexpressed in AML and confers an inferior overall survival compared to CD200low/neg patients. Here we show that a fully human anti‐CD200 antibody (TTI‐CD200) can block the interaction of CD200 with its receptor and restore AML immune responses in vitro and in vivo .